Additive manufacturing of 3D substrate integrated waveguide components. Issue 18 (1st September 2015) - Moscato, S.; Bahr, R.; Le, T.; Pasian, M.; Bozzi, M.; Perregrini, L.; Tentzeris, M.M.
Abstract : The implementation of fully three‐dimensional (3D) substrate integrated waveguide (SIW) components by using an additive manufacturing technique is demonstrated for the first time. In particular, a 3D printing process based on the t‐glase filament has been adopted. 3D printing allows for the manufacturing of very complex shapes in a few hours, thus leading to a one‐day prototyping time for microwave components. To characterise the electromagnetic properties of the 3D printed material, a microstrip lines technique has been adopted. To fully demonstrate the potential of the proposed fabrication process, a SIW cavity resonator and a 3D SIW interconnect with four E‐plane bends have been fabricated and tested.